Pulmonary arterial stiffness indices assessed by intravascular ultrasound in children with early pulmonary vascular disease: prediction of advanced disease and mortality during 20-year follow-up. (6th March 2017) - Ploegstra, Mark-Jan; Brokelman, Jody G M; Roos-Hesselink, Jolien W; Douwes, Johannes M; van Osch-Gevers, Lenny M; Hoendermis, Elke S; van den Bosch, Annemien E; Witsenburg, Maarten; Bartelds, Beatrijs; Hillege, Hans L; Berger, Rolf M F
Abstract: Aims: Prognosis in children with pulmonary vascular disease (PVD) is closely linked to right ventricular (RV) failure due to increased RV-afterload. Pulmonary arterial (PA) stiffening is known to occur early in the course of PVD and constitutes a main component of RV-afterload. This study aimed to evaluate the clinical value of PA-stiffness in children with PVD by determining its association with advanced pulmonary arterial hypertension (PAH) and mortality at long-term follow-up. Methods and results: Forty-one children with various stages of arterial PVD, defined as mean PA-pressure  ≥20 mmHg and/or pulmonary-to-systemic flow-ratio  ≥1.2, and mean pulmonary capillary wedge pressure  <15 mmHg, underwent cardiac catheterization with intravascular ultrasound (IVUS) imaging between 1994 and 1997 with follow-up until 2015. PA-stiffness indices evaluated were PA-area-compliance (PA-compliance) and PA-area-distensibility (PA-distensibility). During follow-up, advanced PAH was determined by echocardiography and cardiac catheterization. During a median follow-up of 19 years, in 31 (76%) patients PVD had reversed and 10 (24%) had advanced PAH. Six (15%) died due to PVD. In addition to conventional haemodynamics, PA-compliance and PA-distensibility were associated with advanced PAH at long-term follow-up (adjusted OR [95% CI] 0.56 [0.37–0.85] and 0.52 [0.31–0.86]), and mortality (adjusted HR [95% CI] 0.60 [0.41–0.87] and 0.67 [0.49–0.90]). Also in a subgroup of patients with favourable haemodynamics, baseline PA-compliance and PA-distensibility were lower in patients with advanced PAH at follow-up ( P   =  0.002 / P  =  0.030). Conclusion: In children with PVD, PA-stiffness indices assessed by IVUS predict advanced PAH and mortality at long term follow-up. Especially in patients with favourable haemodynamics, assessment of intrinsic PA-stiffness may enhance the prognostication of disease progression and survival.